Critical psychology: A territorial imperative - Miller, Ronnie (PINS-Psychology in Society, 2025)
Cultural relativism is a luxury third world countries cannot afford. With the possible exception of South Africa’s apartheid policies, no third world country would seriously attempt to implement social policies based on the notion formulated by the Laboratory of Comparative Human Cognition that "all cultures have to be considered equally effective in producing ways of dealing with the problems of survival of our species under unique patterns of constraint" (1982, p.710). Quite apart from the awesome spectacle that some cultures appear to be considerably more effective in the ways they have produced to exterminate the species, the doctrine of cultural relativism has a hollow ring for people for whom the harsh realities of survival include famine, disease, oppression, and exploitation. But, perhaps, it is unfair to judge cultural relativism by what it says and, instead, it should be understood as an injunction to psychologists who conduct research in remote places away from home that they do not come from a privileged place. What this means is not necessarily that people always and everywhere are equally good at survival but only and importantly that psychologists should refrain from judging and ranking others because to do so is to come from a privileged place. Taken literally, however, cultural relativism is a truism of a singularly uninformative kind for both the development of scientific enquiry and for human emancipation.